2023
DOI: 10.1093/haschl/qxad016
|View full text |Cite
|
Sign up to set email alerts
|

Critical gaps in understanding firearm suicide in Hispanic communities: demographics, mental health, and access to care

Abstract: Suicide rates increased by 26.7% among Hispanics from 2015-2020, driven at least in part by highly-lethal firearm suicide deaths. However, there are critical gaps in characterizing firearm suicide risks and prevention opportunities in Hispanic communities. We examined Hispanic adult firearm suicide decedents reported through the National Violent Death Reporting System from 2013-2019, focusing on demographic characteristics, firearm choices, suicidal thoughts/behaviors, mental health, and mental health treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Critically, little is known about the epidemiology of firearm suicide death within Latina/o/x populations ( 9 ). In general, access to firearms – the most common and lethal method of suicide death ( 10 , 11 ) – exacerbates suicide risk ( 12 , 13 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Critically, little is known about the epidemiology of firearm suicide death within Latina/o/x populations ( 9 ). In general, access to firearms – the most common and lethal method of suicide death ( 10 , 11 ) – exacerbates suicide risk ( 12 , 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…The authors found that, although there was a higher suicide rate in rural Maryland counties than urban counties, the difference in the suicide rate was limited to firearm suicide deaths and did not exist when only evaluating non-firearm suicide deaths. Other recent studies examining large, national samples of firearm suicide decedents have indicated that Latina/o/x and non-Latina/o/x firearm suicide decedents typically differ demographically (e.g., younger) ( 9 ). However, despite Latina/o/x individuals currently representing the largest share of the rural minority population in the U.S. ( 24 ), previous studies have not specifically investigated whether or why firearm suicide rates differ between Latina/o/x and non-Latina/o/x individuals in rural areas.…”
Section: Introductionmentioning
confidence: 99%
“…Access and connection to care is limited for individuals at risk for suicide, with a recent meta-analysis suggesting that fewer than 26% of individuals who died by suicide had contact with inpatient or outpatient mental health services within the year prior to their death [17,18]. Barriers to accessing mental healthcare services disproportionately impact certain populations, such as those in rural areas and minority populations [19,20]. To mitigate such barriers and enhance access within a stepped-care model, digital interventions and telehealth treatments have been identified as valuable care options [19,21,22].…”
Section: Introductionmentioning
confidence: 99%